PSYCHIATRIC MORBIDITY AMONGST THE TROOPS DEPLOYED AT SIACHEN - Bashir, Khalid (Pakistan Armed Forces Medical Journal, 2018)
Objectives: To compare the psychiatric morbidity in acclimatized “deployed” troops with acclimatized but “not yet deployed” troops and to find out the usefulness of General Health Questionnaire – 12, as a screening tool to identify psychiatric morbidity in troops at high altitudes.  Study Design: Comparative study.Duration and Place: The study was conducted at Siachen from June to July 1996.Patients and Methods: The study population (n= 245) was divided into two groups. Group I (n=126) comprised of troops acclimatized and trained for 07 weeks below 14000 feet by staged and graded ascent but were “not yet deployed”, and Group II (n=119) comprised of acclimatized troops who remained “deployed” above 15000 feet for an average duration of 07 weeks, and had descended to a mean height of 14200 feet, in previous two - three weeks. General Health Questionnaire – 12 and Present State Examination were used for psychiatric evaluation. Results: Out of 245 troops exposed to high altitude, 105 (42.8%), had psychiatric morbidity, as measured by a score of more than 2 on General Health Questionnaire -12 and a positive International Classification of Diseases – 10 diagnosed on clinical psychiatric interview based on Present State Examination. More troops 67 (56.3%), in Group II had psychiatric morbidity as compared to Group I, 38 (30.2%). Psychotic symptoms; delusions 2 (1.68%) and hallucinations 3 (2.52%) were seen in Group II patients whereas no psychotic symptoms were seen in Group I. The psychotic symptoms resolved completely after descending to 14200 feet but the neurotic symptoms, did not resolve completely. Cases, scoring 2/12 or above (42.8%) on General Health Questionnaire -12 were highly associated with a positive psychiatric diagnosis. The sensitivity, specificity and Positive Predictive Value and Negative Predictive Value of GHQ-12 in group I was 100%, 91%, 82.6% and 100%; whereas in group II it was 100%, 98.1%, 98.5% and 100% respectively.Conclusion: High altitude “deployment” is stressful for troops and is associated with development of “psychotic and “neurotic” symptoms above 15000 feet. The “psychotic” symptoms abate completely but some “neurotic” symptoms persist even after descent to 14200 feet. General Health Questionnaire – 12 followed by psychiatric interview can effectively determine psychiatric morbidity in troops deployed at high altitudes.